JURIDICAL REVIEW OF BUILDING RIGHTS EXTENSION ON MANAGEMENT RIGHTS - Herlina Hanum Harahap; Danial Syah (International Journal of Law Reconstruction, 2021)
The term of Building Use Rights on Management Rights was initially for 50 years in accordance with the provisions of Article 35 of Act No. 5 of 1960 but with the existence of Article 29 of Government Regulation Number 27 of 2014 to five 5 years. This clearly results in the issue of legal uncertainty for holders of Building Use Rights over Management Rights. The method used is normative juridical, the results of research obtained based on the analysis carried out can be seen that so far the arrangement for extension of Building Use Rights over Management Rights cannot be separated from the provisions of Article 35 of Act No. 5 of 1960, namely 30 years which can be extended with an approved for 20 years, with the provision of Article 29 of Government Regulation Number 27 of 2014 on Management of State and/or Regional Property, it has clearly changed the length of time granting Building Use Rights over Management Rights, namely for five years which can be extended with government approval. The provisions of Article 29 of Government Regulation Number 27 of 2014 on Management of State and/or Regional Property have resulted in legal certainty issues and can harm the holders of Building Use Rights above management rights so that it is clear that the provisions including Verordnung & Autonome Satzung have contradicted the provisions.